(3GdhGVM aj GdeMGSHI GdbWGYjIs (3GdHfGA hGdCTZGd GdYehejIs - (3Hf QHjY(B, (3MfjaIs ((3GdLRGFQs, 2023)
(3jMJhj gPG GdcJGH Ydi eGjdj(B: (3eONd dfTGW bWGY GdebGhdGJ,CSGSjGJ eMGSHI bWGY GdebGhdGJ, GdJSLjdGJ GdeMGSHjI hab ELQGA JfajP YbhO GdebGhdGJ, heY JeGQjf JWHjbjI eMdhdI(B.s
Keywords: (3GdeMGSHIs